Radioterapia em tumores hipofisários. - Carla Baptista; Isabel Paiva; Leonor Gomes; Fernando Gomes; Manuela Carvalheiro; M M Almeida Ruas (Acta Médica Portuguesa, 2002)
The aim of this study is to evaluate the use of conventional external radiotherapy in patients with pituitary adenomas. Between October 1970 and May 1998, 27 patients with pituitary adenoma were followed at the Department of Endocrinology and Diabetes of the Hospitais da Universidade de Coimbra. They received radiation therapy at Instituto Português de Oncologia. Seven of those tumors were classified as nonfunctioning adenomas, 17 as growth-hormone-secreting adenomas, 2 as prolactinomas and 1 as adrenocorticotropic adenoma. Twenty-six patients received radiation as adjuvant therapy after incomplete resection and one patient as primary treatment. The majority of these cases were treated using the parallel opposed-field technique with a total dose between 45 and 52 Gy. The patients were submitted, before and after radiotherapy, to a protocol in order to assess the efficacy of this treatment. Some of the results were analyzed. Reduction of tumor mass was achieved in 66.6% of nonfunctioning tumors and in 25% of the secreting ones. Reduction or stabilization of hormonal levels was achieved in 55% of the cases and normalization in 30%. The average duration of follow-up was 126.3 months. Complications observed: hypopituitarism, stroke (3 patients), cerebral edema (1 patient), memory loss (2 patients) and hearing loss (2 patients). None of the patients developed brain tumors.